Acoustic Analysis of the Speech in Normal Adults - Gopal N.K (Journal of All India Institute of Speech and Hearing, 1970)
Speech is a neuromuscular activity. Tn other words, the output of this activity is the acoustic signals, which are used for communication—as speech. The acousticcharacteristics of speech have been found to vary with age. These acoustic characteristics on various aspects of speech production indicate the accuracy of controlchanges with the age.